1998
DOI: 10.1016/s0927-6505(98)00031-0
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of cosmic ray composition measurements at the highest energies

Abstract: In recent years the Fly's Eye and Akeno groups have presented analyses of the cosmic ray mass composition at energies above 10 17 eV. While the analysis of the Fly's Eye group points to a likely change in mass composition from heavy to light at energies above 10 18 eV, the Akeno analysis favours an unchanging composition. However, the two groups base their conclusions on simulations using quite different hadronic models. Here we present a comparison of the experiments using the same hadronic model and find tha… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
51
0

Year Published

2000
2000
2011
2011

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(55 citation statements)
references
References 9 publications
4
51
0
Order By: Relevance
“…Taking ρ µ ∝ E β , data gives β = 0.84 ± 0.02 [4,9], while from simulation β ∼ 0.9 (β = 0.92 (0.89) for protons with QGSJET (SIBYLL), while for Fe β = 0.88 (0.87) [4]). It has been argued [12] that these results can be interpreted as a change in composition from heavy (at around 10 17.5 eV) to light (at around 10 19 eV), agreeing with the Fly's Eye indication. It has been pointed out in [4] that this interpretation should be studied in a wider energy range, as it seems to lead to a composition heavier than Fe at lower energies.…”
Section: Experimental Statussupporting
confidence: 78%
“…Taking ρ µ ∝ E β , data gives β = 0.84 ± 0.02 [4,9], while from simulation β ∼ 0.9 (β = 0.92 (0.89) for protons with QGSJET (SIBYLL), while for Fe β = 0.88 (0.87) [4]). It has been argued [12] that these results can be interpreted as a change in composition from heavy (at around 10 17.5 eV) to light (at around 10 19 eV), agreeing with the Fly's Eye indication. It has been pointed out in [4] that this interpretation should be studied in a wider energy range, as it seems to lead to a composition heavier than Fe at lower energies.…”
Section: Experimental Statussupporting
confidence: 78%
“…Initially the conclusion of the AGASA experiment was quite opposite to the Fly's Eye: no change in chemical composition. However a recent critical review of both methods 33 showed that the inconsistencies were mainly due to the scaling assumption of the interaction model used by the AGASA group. The authors concluded that if a model with a higher (compared to the one given by scaling) rate of energy dissipation at high energy is assumed, as indicated by the direct X max measurements of the Fly's Eye, both data sets demonstrate a change of composition, a shift from heavy (iron) at 0.1 EeV to light (proton) at 10 EeV.…”
Section: The Chemical Compositionmentioning
confidence: 99%
“…They introduce large and difficult to quantify systematic uncertainties on many cosmic ray analyses. This is a well known problem for the primary energy spectrum as derived from Monte Carlo calibrated surface detector data [1][2][3][4][5][6], as well as for the determination of the primary mass composition of high energy cosmic rays [5,[7][8][9][10][11]. The model-dependence of the interpretation of air shower data is mainly related to the differing predictions of the number of muons in air showers and the depth of the shower maximum [12].…”
Section: Introductionmentioning
confidence: 99%